Effect of single dose preemptive intravenous paracetamol, dexamethasone, and magnesium sulfate on perioperative hemodynamic variables and post-operative nausea, vomiting, and pain in open cholecystectomy done under general anesthesia: A prospective, randomized, and single-blind study - Dilip Kothari; Sivaranjani S; Rajat Sharma; Upendra Rai (Asian Journal of Medical Sciences, 2023)
Background: Pain due to open cholecystectomy can result in delayed recovery and poor operative outcomes. Multimodal approaches to pain control cause functional improvement. We compared the efficacy of paracetamol 1 g, dexamethasone 8 mg, and magnesium sulfate 2 g with normal saline in control over perioperative hemodynamics and post-operative pain in patients undergoing open cholecystectomy under general anesthesia. Aims and Objectives: This study conducted to assess the effect of preemptive intravenous paracetamol, dexamethasone, and magnesium sulfate on perioperative hemodynamic variables (primary outcome) and post-operative nausea, vomiting, and pain (secondary outcome) in open cholecystectomy. Materials and Methods: Sixty patients of ASA Grade I/II were randomized into two groups to receive either normal saline 100 ml iv (Group C, n=30) or infusion containing inj. paracetamol 1 g, inj. dexamethasone 8 mg and inj. magnesium sulfate 2 g iv (group PDM, n=30), 20 min before induction. Intraoperative and post-operative hemodynamic data, post-operative pain scores, and incidence of nausea vomiting were recorded. Results: Intraoperative pulse rate was significantly higher at intubation and 15 min after intubation in the control group and intraoperative systolic, diastolic, and mean arterial blood pressure were significantly higher in control group at intubation and until 60 min. Post-operative pulse rate was significantly higher in the control groups at 180 min and incidence of PONV reduced in PDM group until 90 min. Conclusion: Preemptive intravenous infusion of paracetamol, dexamethasone, and magnesium sulfate provided better stability over perioperative hemodynamics, reduced the incidence of post-operative nausea vomiting, and provided better post-operative pain control.